KEPUASAN PENGGUNA ATAS LAYANAN WEBSITE DITINJAU DARI ASPEK DESAIN WEB DAN KUALITAS INFORMASI PADA WEBSITE - Rahmi, Palupi Permata (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2021)
This study discusses the importance of using the internet to improve competitiveness with other universities. School of Economics (STIE) INABA Bandung has a website that is www.inaba.ac.id that serves as a communication medium that can provide information for students, lecturers, and the general public. This research was made to analyze the effect of website design and the quality of information on user satisfaction over website service by distributing 39 questionnaires to postgraduate students of semester 1 academic year of Management Studies 2020 as respondents. This research uses a quantitative method. Using the structural equation method model - partial least square SEM - PLS. Research shows that website design and quality of information affect user satisfaction over website services. Keywords: User Satisfaction, Web Design, Information Quality, Innovation Value, Technology, SEM, PLS.